2017
DOI: 10.18632/oncotarget.16397
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of circulating endothelial cells in metastatic colorectal cancer

Abstract: BACKGROUNDThere is urgent need for improved staging in patients with metastatic colorectal cancer (mCRC). In this study, we evaluated the prognostic value of circulating endothelial cells (CEC) in comparison with circulating tumor cells (CTC) in patients with mCRC amenable for potentially curative surgery.METHODSA total of 140 patients were enrolled prospectively. CTC and CEC were measured with the CellSearch System (Veridex, NJ, USA). Cut-off values were determined using ROC analyses. Prognostic factors were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 49 publications
(49 reference statements)
1
16
1
Order By: Relevance
“…Studies from CEC counts prior to liver resections reported 5/mL (CellSearch, 140 patients) or 10 vs. 20/mL for patients with respectively good (n = 102) or poor (n = 52) outcome, (CD34 + CD45 − CD146 + measured by FACS). [20,21]. In this study, a significant higher CEC count after three cycles of chemotherapy (p = 0.00), with a nearly 2-fold increase (48 to 90/4 mL) was detected.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Studies from CEC counts prior to liver resections reported 5/mL (CellSearch, 140 patients) or 10 vs. 20/mL for patients with respectively good (n = 102) or poor (n = 52) outcome, (CD34 + CD45 − CD146 + measured by FACS). [20,21]. In this study, a significant higher CEC count after three cycles of chemotherapy (p = 0.00), with a nearly 2-fold increase (48 to 90/4 mL) was detected.…”
Section: Discussionsupporting
confidence: 52%
“…Both studies used the CellSearch system (by Veridex ® , Menarini Silicon Biosystems Inc. Huntington Valley, PA 19006, USA), one showing no prognostic value for PFS or OS [18], the other increase of PFS and OS for baseline CEC counts < 65/mL [19]. In a third prospective series, CEC ≤ 21/4 mL was found to be an independent prognostic factor of poor survival for patients with mCRC amenable for potentially curative surgery, which was of stronger prognostic value than circulating tumor cells [20]. The flow cytometry enumeration we used, as described before by Kraan et al has the same markers for CEC identification, albeit with different fluorescent antibodies.…”
Section: Discussionmentioning
confidence: 95%
“…This notion was supported by Ilie et al [78] who investigated the usefulness of CD164+ circulating EnC counting in combination with CD164 serum level detection for predicting clinical outcomes in non-small cell lung carcinoma patients undergoing surgery, showing that marker elevation in both cases at baseline correlated positively with poor prognosis. Similar investigations with respect to the detection platform and outcome have been conducted for breast and colorectal cancer [60,83]. Moreover, Rahbari et al [83] compared circulating EnC with epithelial CTC for prognostic performance in metastatic colorectal cancer using the CellSearch system.…”
Section: Endothelial Cell Clinical Usementioning
confidence: 86%
“…Similar investigations with respect to the detection platform and outcome have been conducted for breast and colorectal cancer [60,83]. Moreover, Rahbari et al [83] compared circulating EnC with epithelial CTC for prognostic performance in metastatic colorectal cancer using the CellSearch system. The authors reported a higher hazard ratio associated with overall survival (OS) in case of circulating EnC when compared to CTC.…”
Section: Endothelial Cell Clinical Usementioning
confidence: 86%
See 1 more Smart Citation